The Invention of Tradition of Folk Festivals in the Context of Urban Revitalization: A Case Study of the Peony Culture Festival in Luoyang China - Chen , Yuxiao; Sirisuk, Metta (Journal of Roi Kaensarn Academi, 2024)
"Luoyang Peony is peerless in the world". Modern Luoyang people have "invented" the regional unique peony festival ceremony and peony festival culture based on the symbolic peony cultural tradition of the region, which contains rich and diverse connotations and has become a cultural gateway for people to understand the region. In this study, qualitative research methods are used and the representative Peony Cultural Festival in Luoyang is taken as a case study. The objectives of this study are: (1) to study the process of formation, development, restoration and invention of the Luoyang Peony Cultural Festival using the theory of "Invention of Tradition"; (2) to study the promotion of the Luoyang Peony Cultural Festival to the urban renaissance of Luoyang using the theory of "Urban Revitalization". The literature method, general interview method and participant observation method were used to obtain research information. Research findings: (1) The Luoyang Peony Cultural Festival is not a fresh invention, but a tradition invented under the inheritance of the Luoyang peony culture; (2) In contemporary times, the Luoyang Peony Cultural Festival continues to form new inventions that continue to be inherited, and the Festival promotes the development of the city of Luoyang in terms of the economy, culture, and urban environment.